2015
DOI: 10.1002/pola.27708
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and thermoresponsive properties of Helical Polypeptides Derivatized from Poly(γ−4‐(3‐chloropropoxycarbonyl)benzyl‐L‐glutamate)

Abstract: A series of side-chain-functionalized a-helical polypeptides, i.e., poly (c-4-(3-chloropropoxycarbonyl)benzyl-L -glutamate) (6) have been prepared from n-butylamine initiated ring-opening polymerization (ROP) of c-4-(3-chloropropoxycarbonyl)benzyl-L -glutamic acid-based N-carboxyanhydride. Polypeptides bearing oligo-ethylene-glycol (OEG) groups or 1-butylimidazolium salts were prepared from 6 via coppermediated [213] alkyne-azide 1,3-dipolar cycloaddition or nuleophilic substitution, respectively. CD and FTIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…However, they cannot dissolve in DI H 2 O, which is different from the reported polypeptides with OEG pendants that showed LCST‐type phase behaviors in aqueous solutions . OEGylated poly(γ‐benzyl‐ l ‐glutamate)s prepared by 1,3‐dipolar cycloaddition showed LCST‐type phase behaviors when the degree of polymerizaiton of OEG was 3 (i.e., m = 3) while 5b samples showed poor water solubility likely because of the hydrophilicity of 1,3,4‐triazole rings in the former samples. It is interesting to observe that 5a and 5b samples showed an UCST‐type phase behaviors in a variety of alcoholic solvents, including methanol [Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, they cannot dissolve in DI H 2 O, which is different from the reported polypeptides with OEG pendants that showed LCST‐type phase behaviors in aqueous solutions . OEGylated poly(γ‐benzyl‐ l ‐glutamate)s prepared by 1,3‐dipolar cycloaddition showed LCST‐type phase behaviors when the degree of polymerizaiton of OEG was 3 (i.e., m = 3) while 5b samples showed poor water solubility likely because of the hydrophilicity of 1,3,4‐triazole rings in the former samples. It is interesting to observe that 5a and 5b samples showed an UCST‐type phase behaviors in a variety of alcoholic solvents, including methanol [Fig.…”
Section: Resultsmentioning
confidence: 70%
“…They have gained increasing attention due to their significant potential application as biomedical materials (e.g., nanoparticles or hydrogels with controlled drug release) . Very recently, we have demonstrated that OEGylated poly(γ‐benzyl‐ l ‐glutamate)s (i.e., PBLG‐OEG 2/3 ) prepared in an eight‐step synthetic route (e.g., ROP and 1,3‐dipolar cycloaddition) showed UCST‐type phase behavior in water, methanol, and ethanol depending on the main‐chain and side‐chain lengths . We reasoned that the α‐helical poly(γ‐benzyl‐ l ‐glutamate) main‐chain and the length of main‐/side‐chains played an important role in the thermoresponsive properties in organic media.…”
Section: Introductionmentioning
confidence: 99%
“…In the typical GPC chromatograms (Fig. 5), an obvious peak shift can be observed by comparing PMSELG 20 with PMSELG 20 -g-OEG 4 A 5 and PMSELG 20 -g-OEG 4 A 15 , suggesting an increase of molecular weight after grafting OEGA. In addition, the PDI of the obtained graft polypeptides was relatively low (M w /M n 5 1.2-1.3) and the GPC trace was symmetric, which indicated OEGA was successfully grafted from the polyglutamate backbone in a highly controlled manner by RAFT polymerization.…”
Section: Nmr and Maldi-tof-ms Resultsmentioning
confidence: 91%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Particularly interesting are thermoresponsive polypeptides, which can change their conformation or secondary structure in response to the temperature change. [20][21][22][23][24] Many studies have been done to prepare thermoresponsive polypeptides in recent years. [25][26][27][28][29] Li employed direct ringopening polymerization (ROP) of pegylated-L-glutamic acid N-carboxyanhydride (NCA) with different oligo(ethylene glycol) (OEG) lengths to synthesize the first thermoresponsive polypeptide in 2011.…”
mentioning
confidence: 99%
“…Recently, stimuli‐responsive polypeptides with responsiveness to pH, temperature, light, oxidation, and gas have gained increased attention for their great potential as smart biomaterials . While thermoresponsive polypeptides with LCSTs have been intensively studied, thermoresponsive polypeptides with UCSTs have been less investigated . For example, polypeptides with ionic liquid pendants (e.g., imidazolium or pyridinium) showed UCST‐type phase behaviors in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%